Inactivation of Escherichia coli O157:H7, salmonellae, and Campylobacter jejuni in raw ground beef by gamma irradiation. - Clavero, M R (1994)
Raw ground beef patties inoculated with stationary-phase cells of Escherichia coli O157:H7, salmonellae, or Campylobacter jejuni were subjected to gamma irradiation (60Co) treatment, with doses ranging from 0 to 2.52 kGy. The influence of two levels of fat (8 to 14% [low fat] and 27 to 28% [high fat]) and temperature (frozen [-17 to -15 degrees C] and refrigerated [3 to 5 degrees C]) on the inactivation of each pathogen by irradiation was investigated. In ascending order of irradiation resistance, the D10 values ranged from 0.175 to 0.235 kGy (C. jejuni), from 0.241 to 0.307 kGy (E. coli O157:H7), and from 0.618 to 0.800 kGy (salmonellae). Statistical analysis revealed that E. coli O157:H7 had a significantly (P < 0.05) higher D10 value when irradiated at -17 to -15 degrees C than when irradiated at 3 to 5 degrees C. Regardless of the temperature during irradiation, the level of fat did not have a significant effect on the D10 value. Salmonellae behaved like E. coli O157:H7 in low-fat beef, but temperature did not have a significant effect when the pathogen was irradiated in high-fat ground beef. Significantly higher D10 values were calculated for C. jejuni irradiated in frozen than in refrigerated low-fat beef. C. jejuni was more resistant to irradiation in low-fat beef than in high-fat beef when treatment was at -17 to -15 degrees C. Regardless of the fat level and temperature during inactivation, these pathogens were highly sensitive to gamma irradiation.(ABSTRACT TRUNCATED AT 250 WORDS)